PROFESSIONALIZATION OF THE TEACHING CAREER IN PRE-UNIVERSITY EDUCATION - Constanța POPESCU; Roxana SURCEL (GEORGESCU) (Business Excellence and Management, 2016)
The governing strategy for education 2016-2020 relies on major investments in human resources, investments made both for professionalization of the teaching career and for reconsideration of the didactical levels system. The community’s expectations in terms of teaching staff’s skills are high. Teachers qualify for one or two speciality disciplines which means a high level of academic education. Knowledge is continuously updated through improvement programmes which ensure a minimum number of 90 transferable credits every 5 years. The traditional role of the information sender is obsolete. There emerge new roles of the modern teacher: resource person, instructor and adviser towards documentation and information, supporter of transdisciplinarity, expert in learning situations presented to pupils, researcher with innovation valences in the discipline didactics, assessor of the learning progress of each pupil, responsible and organiser of the interpersonal relationships which are established in schools or intermediary of such relations with community. The objective of the focus group research as investigation method was to outline the perception of the teaching staff in pre-university education in Dambovita on the “professionalization” model of the teaching career. The sample of the teaching staff in pre-university education, high school, on which the focus group research was conducted, was made up 9 teachers with different expertise, seniority and qualification levels in education so as to ensure representativity and lead to pertinent conclusions with regards to skills which teachers in pre-university education should have in order to practice the teaching profession.